Capture Myopathy in Wildlife: Pathophysiology, Clinical Management and Therapeutic Interventions – A Review - Rokde, Amol; Pradhan, Shiwanee; Adep, Vishal; Kasambe, Vedant; Sengar, Abhay (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Capture myopathy constitutes a severe pathological condition manifesting in wild fauna following pursuit, entrapment, physical restraint,  live stranding events, or transportation procedures. This multi-systemic disorder exhibits significant morbidity and mortality rates across  affected species. While all wild vertebrates demonstrate susceptibility, certain taxonomic groups exhibit sensitive predisposition to  this condition. Diagnostic protocols rely predominantly on behavioral assessment, comprehensive case history analysis, and clinical  symptoms; however, definitive diagnosis frequently requires post-mortem examination. Therapeutic interventions primarily encompass  fluid resuscitation, analgesic management, and rehabilitative physiotherapy protocols.
Keywords: myopathy; constitutes; pathological; manifesting